The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.2174/138161208786071218
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Statins in Preventing the Progression of Congestive Heart Failure in Patients with Metabolic Syndrome

Abstract: Heart Failure (CHF) is a very important public health problem in the world and certainly one of the most common debilitating diseases and cause of mortality. Current knowledge underlines that incidence rates are also influenced by the coexisting pathologic conditions that accelerate the development of disease or increase its severity. Important scientific evidence is emerging to demonstrate a strong correlation between HF and the metabolic syndrome (MetS). Hypolipemia-inducing medication offers the opportunity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Regarded such premises, the new HFPEF paradigm supports the use of statins that exert rapid and direct effects on endothelial redox balance, which are independent of low‐density lipoprotein lowering and consist of reduced superoxide anion production and restored NO bioavailability. Several studies in hypercholesterolemic patients with CAD have demonstrated that lipid lowering therapy restores coronary endothelium‐dependent vasodilatation and increase myocardial perfusion .…”
Section: Discussionmentioning
confidence: 99%
“…Regarded such premises, the new HFPEF paradigm supports the use of statins that exert rapid and direct effects on endothelial redox balance, which are independent of low‐density lipoprotein lowering and consist of reduced superoxide anion production and restored NO bioavailability. Several studies in hypercholesterolemic patients with CAD have demonstrated that lipid lowering therapy restores coronary endothelium‐dependent vasodilatation and increase myocardial perfusion .…”
Section: Discussionmentioning
confidence: 99%
“…It reaffirms the central and irreplaceable role of statins, and represents the drug of choice for blood the control of cholesterol. [36][37][38] The guidelines clearly state that the benefits trials are independent from the type of statin and, therefore, the choice of the latter must be considered in relation to the entity of the reduction required in the individual patient, as well as the efficacy and tolerability to the molecule.…”
Section: Discussionmentioning
confidence: 99%
“…It reaffirms the central and irreplaceable role of statins, and represents the drug of choice for blood the control of cholesterol. [36][37][38] The guidelines clearly state that the benefits trials are independent from the type of statin and, therefore, the choice of the latter must be considered in relation to the entity of the reduction required in the individual patient, as well as the efficacy and tolerability to the molecule.…”
Section: Discussionmentioning
confidence: 99%